The Little Data Book on Private Sector Development 2011 - World Bank (World Bank, 2012)
The little data book on private sector development 2011 is based on world development indicators 2011 and it's accompanying CD-ROM, with a focus on the private sector in development. Access to reliable cross-country data on private sector development is crucial when formulating responses to economic crisis. When downturns affect exports, investment and growth negatively, making life easier for business is a significant step towards economic recovery. This became very obvious during the global financial crises when governments were trying to stimulate economic growth through the creation of more robust private and finance markets. Improving the investment climate facilitates economic adjustment as it helps attract capital to create jobs and provide basic services. The data sources presented in this book report on the scope and types of regulations that enhance and constrain business activity and provide information on business owners' assessment of the business environment. The data have led to new research, enabled benchmarking, and informed the reform process in many developing countries. Included in this guide are indicators on the economic and social context, the investment climate, private sector investment, finance and banking, and infrastructure. Though a pocket guide cannot include all relevant variables, the indicators that are included provide users with a general understanding of the private sector in each country. Indicators displayed in the tables are defined in the Glossary, which also lists data sources.